The use of medications in an aging society: a literary review (Research, Society and Development, 2021)
The aging society is more likely to have diseases and/or pain as a result of the limitations caused by aging. The quickest and most easily accessible solution to delay disease symptoms and relieve pain is the use of medication. This study aims to characterize the use of medication by the elderly, analyze the factors that influence this process and identify the consequences of the use of medication by the elderly, through a literature review with a qualitative approach. The results obtained were the habit of self-medication, the improper disposal of drugs and the practice of polypharmacy, which are influenced by advertisements seen in the media, popular practices and inefficiency of the public health system, which result in drug interactions and adverse reactions.